An evaluation of housing options for military families - Buddin, Richard J., 1951- (RAND, 1999)
Military family housing is a significant-and expensive-benefit, costing the Department of Defense (DoD) nearly $10 billion annually. Because most housing studies have focused on the cost of on-base housing versus the cost of providing allowances for rented or owned off-base housing, the authors investigated the preferences of military families for types of housing and the factors that influence their choices. Service members report that the economic benefits of on-base housing are the most significant factor by far in housing preference, perceiving a vast difference in value between military housing and off-base housing allowances. All other factors, such as a supportive sense of military community, lag far behind economy in influencing choice. Closing the gap in economic disparity between on- and off-base housing, and enhancing programs that aid service members in procuring off-base accommodations, would provide the greatest benefit to services and members.